Planar Chiral Organoboranes with Thermoresponsive Emission and Circularly Polarized Luminescence: Integration of Pillar[5]arenes with Boron Chemistry - Chen, Jin‐Fa; Yin, Xiaodong; Wang, Bowen; Zhang, Kai; Meng, Guoyun; Zhang, Songhe; Shi, Yafei; Wang, Nan; Wang, Suning; Chen, Pangkuan (Angewandte Chemie International Edition, 2020)
Enantiopure molecules based on macrocyclic architecture are unique for applications in enantioselective host‐guest recognition, chiral sensing and asymmetric catalysis. Taking advantage of the chiral transfer from the intrinsically planar chirality of pillar[5]arenes, we herein present an efficient and straightforward approach to achieve early examples of highly luminescent chiral systems (P5NN and P5BN). The optical resolution of their enantiomers has been carried out via preparative chiral HPLC, which was ascribed to the molecular functionalization of pillar[5]arenes with π‐conjugated, sterically bulky triarylamine (Ar3N) as an electron donor and triarylborane (Ar3B) as an acceptor. This crucial design enabled investigations of the chiroptical properties, including circular dichroism (CD) and circularly polarized luminescence (CPL) in the solid state. The intramolecular charge transfer (ICT) nature in P5BN afforded an interesting thermochromic shift of the emission over a wide temperature range. Two examples of planar chiral systems were achieved by axial functionalization of a pillar[5]arene with sufficiently bulky, rigid, π‐conjugated and highly luminescent triarylborane and triarylamine moieties, leading to enantiomeric resolution and circularly polarized luminescence (CPL). They represent the first chiral luminescent systems based on planar chiral pillar[5]arenes.